At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

Let g(x) = cos(x/2) - 3x. Let f(x) = 2x + 5. What is g(f(x))?

Sagot :

Answer:

g(f(x)) =  [tex]cos(\frac{2x+5}{2} ) - 6x -15[/tex]

Step-by-step explanation:

Explanation:-

Let g(x) = [tex]cos(\frac{x}{2} ) - 3x[/tex]   and f(x) = 2x +5

g(f(x)) = g( 2x +5)

        =  [tex]cos(\frac{2x+5}{2} ) - 3(2x+5)[/tex]

       =  [tex]cos(\frac{2x+5}{2} ) - 6x -15[/tex]

g(f(x)) =  [tex]cos(\frac{2x+5}{2} ) - 6x -15[/tex]